The "moral codex" of a researcher as a bearer of culture - Minniyakhmetova, Tatiana (Traditiones (Ljubljana), 2012)
All researchers have their own methods of conducting fieldwork and making available information on the culture they have studied. However, a researcher that is simultaneously a bearer of culture must follow at least three principal ethic rules: First, there is knowledge or information that could be available to anyone. Second, there is knowledge or information that the researcher is initiated into, but the researcher is not allowed by the informant to make it available to anyone. Third, there are prohibitions against sharing certain knowledge or information. My research object is a diaspora group and it therefore requires a special approach to fieldwork.
Keywords: ethnology; Etnologija; field work; Terensko delo; Znanstveno raziskovanje; scientific method; methodology; Metodologija